235. In outpatient clinics serving Veterans, antibiotic prescriptions precede a minority of antibiotic-associated adverse events. (31st December 2020) - Wilson, Brigid; Bej, Taissa A; Banks, Richard; Briggs, Janet; Song, Sunah; Jump, Robin; Jump, Robin; Perez, Federico
Abstract: Background: An estimated 30% of antibiotic prescriptions in outpatient settings may be inappropriate. Antibiotic exposure increases an individual's risk of Clostridioides difficile infection (CDI) and acquiring drug-resistant pathogens. To quantify the increased risk of CDI and drug-resistant pathogens posed by antibiotics prescribed in outpatient visits, we examined a two-year cohort of patients seen in primary care clinics at VA Community-Based Outpatient Clinics (CBOC) associated with a large VA Medical Center. Methods: Among patients with an in-person visit at 13 CBOCs in 2018–2019, we examined rates of antibiotic-associated adverse events (AEs), defined as community-onset CDI or acquisition of resistant Gram-negative bacteria (R-GNB), in the 90 days following those visits. For each visit, we used administrative databases to determine if systemic antibiotics were prescribed, if there was an associated infectious diagnosis, and the subsequent occurrence of AEs. We summarized quarterly rates of prescribed antibiotics and AEs, characterized patients with and without AEs, and estimated the risk ratio of AE for an antibiotic prescription. Results: Following 236, 665 primary care visits, we observed 62 and 225 AEs due to CDI and R-GNB, respectively (0.12% combined rate) among 278 patients (5 with both). Patients who developed CDI or R-GNB had a higher Charlson Comorbidity Index (3.6 ± SD 3.0 and 2.68 ± SD 2.7, respectively) compared to those without AEs (0.72 ± SD 1.3; Table ). The rate of new antibiotic prescriptions was 4% in visits without and 10% in visits with a subsequent AE, yielding a risk ratio of 2.5 (95% CI: 1.7–3.7). The rates of both antibiotic prescribing and AE were steady over the examined two-year period (Figure ). Table Figure Conclusion: Among all patients with a CBOC visit between 2018–2019, an AE, defined as CDI or R-GNB acquisition, was observed following only 0.1% of primary care visits. Among patients who experienced an AE, only 10% of primary care visits preceding those events included a new antibiotic prescription. While this analysis does not address antibiotics during inpatient stays or prescribed by specialty clinics, these findings suggest that among Veterans, outpatient antibiotic exposure may have only a modest contribution to the risk of AE. Disclosures: Robin Jump, MD, PhD, Accelerate (Grant/Research Support)Merck (Grant/Research Support)Pfizer (Grant/Research Support, Advisor or Review Panel member)Roche (Advisor or Review Panel member) Federico Perez, MD, MS, Accelerate (Research Grant or Support)Merck (Research Grant or Support)Pfizer (Research Grant or Support)